THE INTERSECTION OF A STRAIGHT LINE AND A CIRCLE. (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
Details with surfaces are often encountered in various industries, especially in the oil production sector, in equipment, machinery, aircraft construction, automotive, ship design, and ensure high strength and reliability of equipment, its parts and assemblies. The points where one line smoothly transitions to another are called junction points. To establish a smooth transition, you need to know the radius of the junction, the center of the junction, and the location of the junction points.